How do German police officers of varying empathy levels react to different styles of interviewing a suspected sex offender? - Baker-Eck, Bianca; Bull, Ray (International Journal of Law Crime and Justice, 2023)
The United Nations' ‘Special Rapporteur on torture and other cruel, inhuman or degrading treatment or punishment’, disseminated an extensive ‘Universal protocol’ on interviewing/interrogation styles in summer 2021. Its implementation across the world is likely to be influenced by current practices in various countries (such as the rapport building and empathy employed). The aims of the present study were (i) to examine German police officers' estimates of suspect interviews in four different styles of suspect interviews (‘humane’, dominant’, ‘theme development’ or ‘neutral’); and (ii) to see whether interviewers' level of empathy is associated with their reactions to the interview styles. There were significant effects found in the dominant interviewing style regarding the participants' estimation of (i) interviewer fairness towards suspect, (ii) interviewer's understanding on suspect's thought-process toward the crime, (iii) whether the interviewer was aggressive, or (iv) humane, and (v) whether the interview was conducted well. Officers' empathy level only had an effect for the dominant interviewing style.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Empathy; German Police; Interviewing style; Investigative interviewing; Police interview